Pathogenesis of Mycobacterium avium infection - Typical responses to an atypical mycobacterium? - Appelberg, R (2006)
Studying infections with Mycobacterium avium in mouse models has allowed the dissection of the antimycobacterial pathways of the mammalian host. Whereas the paradigm of cell-mediated immunity to intracellular pathogens has been confirmed, namely with regard to the pivotal roles of CD4(+) T cells, macrophages, and the IL12-IFN gamma. cytokine axis, atypical features have been uncovered such as the resistance to NO, the involvement of minor players in the induction of type 1 protective immunity (such as TLR2, CD40, and CD30), and the development of immunopathology during the infection with highly virulent strains such as the development of caseous necrosis of granulomas or the progressive emergence of severe lymphopenia.